Contractor practices for managing extended supply chain tiers. Issue 1 (7th January 2014) - Pala, Mesut; Edum-Fotwe, Francis; Ruikar, Kirti; Doughty, Nathan; Peters, Chris
Abstract : Purpose: – The purpose of this paper is to examine how contractor firms manage their relationships with extended supply chain tiers and investigate the range of ICT technologies used to facilitate such practices. Design/methodology/approach: – An on-line questionnaire survey was conducted to gather information about supply chain management operations, supplier relationship management and the ICT technologies used by contractor firms to manage their extended supply chain tiers. Findings: – The extended supply chain relationships of contractor firms are primarily composed of contractual, technical and financial entities, but findings suggest that the vision to consider extended supply chain firms when selecting suppliers are still myopic. Majority of ICT technologies are used between Tier 1 supply chain firms and there is an inconsistency in the number of technologies adopted with the extended supply chain tiers. Despite having a high involvement relationship with Tier 2 downstream firms, findings indicate a lack of use of ICT technologies to manage the organisational, personal and technological interactions with these firms. Research limitations/implications: – On the basis of different relationship types this study develops an initial framework for management of supply chains that are facilitated by relevant ICT technologies. Originality/value: – This paper provides insights into the management of extended supply chain firms by contractor firms from a relationship-centric perspective and develops an initial framework for relationship-centric supply chain management.